PERTARUNGAN â€œREALITASâ€ DALAM FILM: Analisis Cyberspace Film â€œTranscendenceâ€ - Syafi'i, Muhammad; Latifah, Nor (IAIN Samarinda, 2018)
Humanity in the todayâ€™s modern age linked closely to information and communication technology. Advancements in the area of information and communication technology have changed the very basis of human interactions, including the way people make sense of reality. The presence of cyberspace as a second life of humans, according to Mark Slouka, has led to three different understandings of reality, namely: destopian which views pessimistically, optimistic neofuturists, and more critical techno-realists. In this paper, the author will present one reflection on cyberspace displayed in a Movie by Wally Pfister called